Challenging social norms to recraft practices: A Living Lab approach to reducing household energy use in eight European countries. (February 2021) - Sahakian, Marlyne; Rau, Henrike; Grealis, Eoin; Godin, Laurence; Wallenborn, Grégoire; Backhaus, Julia; Friis, Freja; Genus, Audley T; Goggins, Gary; Heaslip, Eimear; Heiskanen, Eva; Iskandarova, Marfuga; et al.
Abstract: ENERGISE is the first large-scale European effort to reduce household energy use through a change initiative that adopted a 'living lab' approach informed by social practice theory. Two challenges were introduced to 306 households in eight countries: to lower indoor temperatures and to reduce laundry cycles. This contribution demonstrates the usefulness of a practice-centered design that takes habits and routines as an entry point for understanding how different 'elements of practices' can be re-crafted. We discuss how a participatory 'living lab' approach that explicitly encouraged deliberation and reflexivity served to sharpen attention on practices as central to change. We discuss how 'doing laundry' and 'keeping warm', as very different types of practices, responded to the change initiative. For laundry, tangible changes in material arrangements, news skills and sensory competencies, and shifts in what is seen as 'normal' proved to be central to reducing wash cycles, including wearing clothes more often, airing them out, using smell to gauge cleanliness, or keeping dirty clothes out of sight. Warming people rather than spaces through added layers and activities, and related shifts in norms around thermal comfort, emerged as crucial steps towards lowering indoor temperatures. Average changes in reported temperatures and wash cycles indicate that reductions are possible, without an emphasis on individuals or technologies as central to change. We end with a discussion on the implications of our approach for energy sufficiency thinking and practice, emphasizing the merits of taking the complexity of everyday life seriously when designing change initiatives.